Kepuasan Masyarakat dalam Layanan Adminduk Desaku Tuntas di Desa Wonosari Kecamatan Wonosari Kabupaten Malang - Okky Natpala Adirama; Suyeno; Langgeng Rachmatullah Putra (Reslaj: Religion Education Social Laa Roiba Journal, 2024)
This research aims to determine level of public satisfaction in Adminduk ‘Desaku Tuntas’ service in Wonosari Village. This research uses quantitative descriptive approach carried out using survey method. This data is calculated in accordance with the provisions for calculating IKM based on PERMENPAN-RB No. 14 of 2017 which consists of 14 indicators. The data collection technique uses questionnaire. The population is people of Wonosari Village who are using Adminduk ‘Desaku Tuntas’ services at Wonosari Village Government office during the observation period (April 2024). The sampling technique uses accidental sampling which refers to PERMENPAN-RB No. 14 of 2017 so that the sample is 150 respondents. The data analysis technique refers to IKM analysis based on PERMENPAN-RB No. 14 of 2017. The result of this research showed that public satisfaction in Adminduk ‘Desaku Tuntas’ service at Wonosari Village Government office is measured based on IKM in terms of administrative services in total from 14 service indicators in the IKM value range of 2.51 to 3.25 with an IKM conversion value between 62.51 to 81.25 which is in ‘good’ quality and service performance category, meaning that public is satisfied with the quality and performance of the service.